2017
DOI: 10.1007/s00210-017-1443-7
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid-3 (TRPV3) activation plays a central role in cardiac fibrosis induced by pressure overload in rats via TGF-β1 pathway

Abstract: Cardiac fibrosis is a common pathologic change along with pressure overload. Recent studies indicated that transient receptor potential (TRP) channels played multiple roles in heart. However, the functional role of transient receptor potential vanilloid-3 (TRPV3) in cardiac fibrosis remained unclear. The present study was designed to investigate the relationship between TRPV3 activation and pressure overload-induced cardiac fibrosis. Pressure overload rats were successfully established by abdominal aortic cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Our previous studies have found that activation of TRPV3 channels can aggravate cardiac fibrosis in the pressure-overloaded rat hearts. 20 The present study further indicated that the expression of TRPV3 protein was signifi- | 1937 of autophagy after TRPV3 knockdown. As we all know, intracellular calcium is an important regulator of autophagy.…”
Section: Trpv3 Gene Is a Target Of Mir-103supporting
confidence: 63%
See 1 more Smart Citation
“…Our previous studies have found that activation of TRPV3 channels can aggravate cardiac fibrosis in the pressure-overloaded rat hearts. 20 The present study further indicated that the expression of TRPV3 protein was signifi- | 1937 of autophagy after TRPV3 knockdown. As we all know, intracellular calcium is an important regulator of autophagy.…”
Section: Trpv3 Gene Is a Target Of Mir-103supporting
confidence: 63%
“…Fluorescence measurements in cardiomyocytes have been described previously . The neonatal rat cardiomyocytes were incubated with a working solution containing 10 μmol L −1 Fluo‐3/AM (acetoxymethyl ester form, Molecular Probes, St. Louis, MO, USA) and 0.03% Pluronic F‐127 at 37°C for 40 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In rats, the TRPV3 activator Carvacrol is capable to increase the fibrosis produced by aortic banding and it potentiates the AngII-induced increase in Ca 2+ concentration as well as the in vitro proliferation of CFs. In contrast, treatment with siRNA directed against TRPV3 reduces the AngII-induced collagen expression [93]. Another TRPV channel, TRPV4, which determines myofibroblast differentiation and fibrosis in the lung [94], was also shown to mediate TGF-β1-induced differentiation of CFs into myofibroblasts [95].…”
Section: Discussionmentioning
confidence: 99%
“…In rat cardiac fibroblasts, the activation of TRPV3 by Carvacrol increases cell proliferation and upregulates the expression of collagen and TGF-β1. In a pressure-overload hypertrophy rat model, Carvacrol activation of TRPV3 exacerbates heart function and increases fibrosis [182,183]. These results suggest that TRPV3 could be involved in TGF-β1-induced fibroblast proliferation during cardiac fibrosis, but additional experiments with knockout mice are required to conclusively define the channel's role.…”
Section: Trpv3 and Cardiac Fibrosismentioning
confidence: 99%
“…TRPV3 is expressed in the peripheral neurons and various other cell types. It has recently been found that TRPV3 is also expressed in cardiac myocytes [182] and fibroblasts [183], as detected by PCR and western blotting (WB). In rat cardiac fibroblasts, the activation of TRPV3 by Carvacrol increases cell proliferation and upregulates the expression of collagen and TGF-β1.…”
Section: Trpv3 and Cardiac Fibrosismentioning
confidence: 99%